Chapter National Qualifications Frameworks as A Policy Instrument for Lifelong Learning in Ghana, Malaysia and Serbia - Turiman, Punia (Studies on Adult Learning and Education, 2020)
The development of national qualifications frameworks (NQFs) around the globe has been influenced by Anglo-Saxon countries and a global policy of intergovernmental organisations. The main aim of this paper is to explore how recently developed NQFs in diverse global contexts-Ghana, Malaysia, and Serbia-fulfil two proclaimed objectives: recognition of prior learning (RPL) and support for lifelong learning. Based on a comparative analysis of official national and international policy documents relevant to the NQFs in these selected countries, conducted using the method of documentary analysis, our findings indicate that despite differences according to type, scope, and stage of development, all three NQFs are used as a policy instrument for lifelong learning on the one hand, while on the other hand, they reinforce a vocational perspective of RPL, lifelong learning, and adult education.